Warfarin Anticoagulation Therapy in Caribbean Hispanics of Puerto Rico: A Candidate Gene Association Study - Claudio-Campos, Karla; Labastida, Aurora; Ramos, Alga; Gaedigk, Andrea; Renta-Torres, Jessicca; Padilla, Dariana; Rivera-Miranda, Giselle; Scott, Stuart A.; Ruaño, Gualberto; Cadilla, Carmen L.; Duconge-Soler, Jorge (Frontiers in Pharmacology, 2017)
Existing algorithms account for 50% of observed variance in warfarin dose requirements after including common polymorphisms. However, they do not perform as well in populations other than Caucasians, in part because some ethno-specific genetic variants are overlooked. The objective of the present study was to identify genetic polymorphisms that can explain variability in warfarin dose requirements among Caribbean Hispanics of Puerto Rico. Next-Generation Sequencing of candidate genes CYP2C9 and VKORC1 and genotyping by DMET® Plus Assay of cardiovascular patients were performed. We also aimed at characterizing the genomic structure and admixture pattern of this study cohort. Our study used the Extreme Discordant Phenotype approach to perform a case-control association analysis. The CYP2C9 variant rs2860905, which was found in all the major haplotypes occurring in the Puerto Rican population, showed stronger association with warfarin sensitivity (<4 mg/day) than common variants CYP2C9*2 and CYP2C9*3. Although, CYP2C9*2 and CYP2C9*3 are separately contained within two of the haplotypes, 10 subjects with the sensitive phenotype were carriers of only the CYP2C9 rs2860905 variant. Other polymorphisms in CES2 and ABCB1 were found to be associated with warfarin resistance. Incorporation of rs2860905 in a regression model (R2 = 0.63, MSE = 0.37) that also includes additional genetics (i.e., VKORC1-1639 G>A; CYP2C9 rs1856908; ABCB1 c.IVS9-44A>G/ rs10276036; CES2 c.269-965A>G/ rs4783745) and non-genetic factors (i.e., hypertension, diabetes and age) showed better prediction of warfarin dose requirements than CYP2C9*2 and CYP2C9*3 combined (partial R2 = 0.132 vs. 0.023 and 0.007, respectively, p < 0.001). The genetic background of Puerto Ricans in the study cohort showed a tri-hybrid admixture pattern, with a slightly higher than expected contribution of Native American ancestry (25%). The genomic diversity of Puerto Ricans is highlighted by the presence of four different major haplotype blocks in the CYP2C9 locus. Although, our findings need further replication, this study contributes to the field by identifying novel genetic variants that increase predictability of stable warfarin dosing among Caribbean Hispanics.